2020
DOI: 10.3390/cells9020401
|View full text |Cite
|
Sign up to set email alerts
|

Probing Carbon Utilization of Cordyceps militaris by Sugar Transportome and Protein Structural Analysis

Abstract: Beyond comparative genomics, we identified 85 sugar transporter genes in Cordyceps militaris, clustering into nine subfamilies as sequence-and phylogenetic-based functional classification, presuming the versatile capability of the fungal growths on a range of sugars. Further analysis of the global gene expression patterns of C. militaris showed 123 genes were significantly expressed across the sucrose, glucose, and xylose cultures. The sugar transporters specific for pentose were then identified by gene-set en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Above, it is not hard to conclude the variations in the distribution and number of SUT genes among filamentous fungi; this difference may be caused by the evolution of different strains in adapting to distinct external environments. Coincidentally, beyond comparative genomics, researchers identified 85 SUTs in C. militaris , which is closed to A. niger , clustering into nine subfamilies [ 14 ]. Moreover, 100 sugar transporter genes in the silkworm Bombyx mori genome (categorized into 11 distinct groups in the phylogenetic tree) and 20 SUT genes were identified from the cassava ( Manihot esculenta ) genome, which were further divided into four clades [ 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Above, it is not hard to conclude the variations in the distribution and number of SUT genes among filamentous fungi; this difference may be caused by the evolution of different strains in adapting to distinct external environments. Coincidentally, beyond comparative genomics, researchers identified 85 SUTs in C. militaris , which is closed to A. niger , clustering into nine subfamilies [ 14 ]. Moreover, 100 sugar transporter genes in the silkworm Bombyx mori genome (categorized into 11 distinct groups in the phylogenetic tree) and 20 SUT genes were identified from the cassava ( Manihot esculenta ) genome, which were further divided into four clades [ 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, different SUT families in Aspergillus niger ( A. niger ) have a dynamic expression pattern during growth on distinct carbon sources and hence enable the organism to adapt to an extremely broad range of environments [ 13 ]. Contrary to A. niger , in response to different carbon sources, Cordyceps militaris ( C. militaris ) SUT genes within each subfamily harbor an analogous expression pattern with the exception of those involved in the pentose subfamily, which were highly expressed in the xylose culture [ 14 ]. Vankuyk et al reported that regulators CreA regulated the expression of SUT genes in A. niger in response to extracellular pH changes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To uncover the reporter metabolites, the previous genome-scale metabolic network (GSMN) of C. militaris ( i NR1329) [ 15 ] was improved by introducing the genes and their associated metabolites and biochemical reactions involved in carotenoid biosynthetic pathway and sugar transport system, as previously reported [ 7 , 14 , 30 ]. The additional genes identified from the first GSMN of C. militaris ( i WV1170) [ 31 ] together with extensive data mining from different databases were newly added into i NR1329, thereby enhancing the gene content of the improved GSMN in this study.…”
Section: Methodsmentioning
confidence: 99%
“…[25] Structural modeling combined with network theory has been widely exploited in studying protein topology and dynamics. [26, 27] The description of protein structure as a structural network provides an efficient tool to dissect complex protein functions. [28] Based on protein structural network model, different topological parameters and algorithms have been developed to describe structural changes associated with mutations.…”
Section: Introductionmentioning
confidence: 99%